KEY POLICIES AND MEASURES OF HIV PREVENTION AND CONTROL AT GLOBAL LEVEL - Baroš, Slađana; Sipetic Grujicic, Sandra (Medicinski podmladak, 2022)
During the last 40 years, the development of medical HIV and AIDS related knowledge has been followed by a coordinated international HIV response, in terms of developing policies and measures for the HIV/AIDS prevention and control based on evidence from public health and clinical studies. The HIV response can be divided into three periods: the period of HIV response establishment (1981-1996); the period of multisectoral response (1996-2007) and the period of strengthening biomedical measures for HIV prevention (2007 and beyond). International policies and recommended HIV prevention measures have undergone a series of transformations, from the establishment of the first organized and coordinated national programs, to the design and implementation of innovative biomedical prevention measures, such as voluntary medical circumcision, pre-exposure prophylaxis and the implementation of the "test and treat" measure - the introduction of antiretroviral therapy immediately after diagnosing HIV infection to achieve undetectable viral load. New findings on successful use of antiretroviral therapy as prevention led to the formulation of goals for 2020: 90% of all people living with HIV to know their HIV status, 90% of them to receive antiretroviral therapy, and 90% of them to have viral suppression; to have less than 500,000 of both newly HIV infected persons, and AIDS related deaths. Despite of the HIV response major improvements, such as development and implementation of multisectoral national HIV/AIDS policies on prevention and control, the 2020 goals have not been meet. For achieving the main goal - ending AIDS as public health treat by 2030, implementation of all recommended biomedical, behavioral and structural interventions should be intensifying.